Mycophenolic acid concentrations in peripheral blood mononuclear cells are associated with the incidence of rejection in renal transplant recipients. (7th August 2018) - Md Dom, Zaipul I.; Coller, Janet K.; Carroll, Robert P.; Tuke, Jonathan; McWhinney, Brett C.; Somogyi, Andrew A.; Sallustio, Benedetta C.
Abstract : Aims: Although therapeutic drug monitoring of plasma mycophenolic acid (MPA) concentrations has been recommended to individualize dosage in transplant recipients, little is known regarding lymphocyte concentrations of MPA, where MPA inhibits inosine monophosphate dehydrogenase (IMPDH). This study investigated the utility of measuring predose MPA concentrations in peripheral blood mononuclear cells (C0C ) and predose IMPDH activity, as predictors of graft rejection in renal transplant recipients. Methods: Forty‐eight patients commencing mycophenolate mofetil (1 g twice daily) in combination with tacrolimus and prednisolone were recruited. Blood was collected for determination of trough total (C0P ) and unbound (C0u ) plasma MPA concentrations. Peripheral blood mononuclear cells were isolated for determination of C0C and IMPDH activity. The incidence of rejection within 2 days of sample collection was determined histologically and classified according to the Banff 2007 criteria. Results: There was no association between MPA C0C and C0P (rs  = 0.28, P  = 0.06), however, MPA C0C were weakly correlated with MPA C0u (rs  = 0.42, P  = 0.013). Multivariate analysis indicated that MPA C0C was the only covariate independently associated with rejection (FDR‐adjusted P  = 0.033). The receiver operating characteristic area under the curve (AUC) for the prediction of severe rejection using MPA C0C was 0.75 ( P  = 0.013), with 73% sensitivity and specificity at a C0C threshold of 0.5 ng 10 –7 cells. However, predose IMPDH activity was not a predictor of rejection ( P  > 0.15). Conclusions: MPA C0C measurement within the early post‐transplant period may be useful to facilitate early titration of MPA dosing to significantly reduce rejection.